2020
DOI: 10.6026/97320630016893
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking analysis of compounds from Justica adhatoda L with glycogen synthase kinase-3 β

Abstract: Type 2 diabetes mellitus (T2DM) is linked with Glycogen synthase kinase-3 β.Therefore, it is ofinterest to document molecular docking analysis data of compounds from Justica adhatoda L with glycogen synthase kinase-3 β. We report the binding features of ethambutol, pyrazinamide, stigmasterol and vasicoline with GSK-3 β.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Among these targets, 20 targets of diosgenin and stigmasterol were identified. Another two targets of diosgenin and stigmasterol, namely, GSK-3β and ESR1, were also included for further analysis according to previous studies ( Jayaraman et al, 2020 ; Wang et al, 2021a ). Besides, 1179 NAFLD-related targets were collected from the GeneCards database, and then verified in the DisGeNET database.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these targets, 20 targets of diosgenin and stigmasterol were identified. Another two targets of diosgenin and stigmasterol, namely, GSK-3β and ESR1, were also included for further analysis according to previous studies ( Jayaraman et al, 2020 ; Wang et al, 2021a ). Besides, 1179 NAFLD-related targets were collected from the GeneCards database, and then verified in the DisGeNET database.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the TCMSP database and encyclopedia of traditional Chinese medicine (ETCM, http://www.tcmip.cn/ETCM/index.php/Home/ ) database were used to obtain the targets of the screened components. The results were then combined with the corresponding literature search results ( Jayaraman et al, 2020 ; Wang et al, 2021a ). Finally, the component targets were integrated into standard gene symbol using the Uniport platform ( https://www.uniprot.org/ ) ( jing et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The compound was also found to have good ADMET properties which provides it with further validation as an anti-viral agent in treating SARS-CoV-2 infection [ 40 , 41 , 42 ]. In a study conducted by Jayaraman et al, they concluded that ethambutol, pyrazinamide, vasicoline and stigmasterol have anti-diabetic effects when docked against Glycogen synthase kinase-3; these compounds were derived from J. adhatoda [ 43 ].…”
Section: Discussionmentioning
confidence: 99%